Empirical Methods in International Trade Using for Evaluation in Export of Services in CEE Countries Based on Balassa Index - BENO Michal (Journal of Economic and Social Development (Varaždin), 2018)
Balassa Index is widely used in the research literature to measure country-sector called Revealed Comparative Advantage (RCA) to determine a country’s weak and strong sectors. In this paper we determine a country’s strong sector by analyzing the actual export flows in services of CEE countries. Our study includes 10 countries based on raw data from the International Trade Center for the period from 2012 till 2016. We provide a systematic analysis of the empirical distribution of the Balassa index. Using analysis, we consider which country in which sector of the service is Rival for chosen 10 countries. It is evident that foreign trade is important for all of them, albeit it to varying degrees. It might seem a logical way to restore economic strength. This paper presents a new approach to the export structure of services using the Balassa Index.